Real‐world implementation of DPYD and UGT1A1 pharmacogenetic testing in a community‐based cancer center - Megan Muldoon; Mollie Beck; Nichlas Sebree; Robin Yoder; Stacey Ritter; Josiah D. Allen; Zuhair Alqahtani; Jaime Grund; Brooke Philips; Kristina Hesse; Nihal El Rouby (Wiley, 2024)
Abstract We set out to demonstrate the feasibility of pharmacogenetic testing of DPYD and UGT1A1 and explore the clinical benefits in a community‐based cancer center. We conducted a retrospective review of 280 patients who underwent pharmacogenetic testing between November 2020 and May 2023. The primary end points included the percentage of patients with results prior to chemotherapy initiation, percentage of DPYD‐ and UGT1A1‐guided interventions implemented before chemotherapy initiation, and the turnaround time (TAT) for the pharmacogenetics results. Exploratory end points included a comparison of unplanned hospitalizations and treatment interruptions among (1) DPD phenotypes in patients who received fluoropyrimidines and (2) UGT1A1 phenotypes in patients who received irinotecan ± fluoropyrimidines. We evaluated cancer progression among patients who received DPYD‐guided dose reductions in the curative setting. More than 75% of patients had results prior to initiation of chemotherapy and 61.5% of the actionable interventions were implemented before chemotherapy, with a median TAT of 7 calendar days (IQR 5-8 calendar days). A non‐significant higher percentage of unplanned hospitalizations and treatment interruptions occurred among patients with normal DPYD compared with patients with DPYD‐guided dose reductions. A non‐significant higher frequency of treatment interruptions and dose reductions were observed in UGT1A1 intermediate metabolizer (IM) compared with UGT1A1 normal metabolizer (NM). None of the patients who received DPYD‐guided dose reductions in the curative setting experienced progression after a median follow‐up of 342 days. The real‐world evidence generated from this study demonstrates the feasibility of pre‐chemotherapy pharmacogenetic testing of DPYD and UGT1A1 in a community‐based cancer center.